Pemanfaatan Instagram sebagai Saluran Komunikasi Pelanggan pada Humas PERUMDA Tirta Musi Palembang - M. Shaka Hidayatullah; Sepriadi Saputra; Sonia Nurprameswari (LPPM Universitas HKBP Nommensen, 2025)
This study aims to analyze the utilization of Instagram as a customer communication channel by the Public Relations division of PERUMDA Tirta Musi Palembang. The development of digital communication has encouraged public service institutions to utilize social media as a medium for delivering information while also building interaction with the community. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews with social media managers, public relations staff, and customers of PERUMDA Tirta Musi. In addition, observations of activities on the official Instagram account and documentation of digital content were conducted to strengthen the research findings. The analysis of this study applies dialogic communication theory which includes the principles of mutuality, propinquity, empathy, risk, and commitment. The results show that Instagram is utilized as a public service communication medium to disseminate information such as announcements of water service disruptions, payment information, and water usage education. Instagram also enables interaction between customers and the organization through the direct message feature. However, the utilization of Instagram still faces several challenges, including limited human resources in managing social media, the potential for misinformation, and the lack of optimal two-way communication due to limited space for public dialogue. Therefore, the management of digital communication through Instagram needs to be optimized so that communication between the organization and its customers can become more effective and responsive.